Perceived Social Position and Income Inequality: Do They Move Together? Evidence from Europe and the United States - Chiara Assunta Ricci (Luxembourg Income Study (LIS), 2016)
The match between perception and reality can depend on many different elements across societies over time, but subjective and objective dimensions are both relevant particularly in social class analysis. The aim of this paper is to investigate perceived social position and income inequality in six different countries between the 1990's and 2000's in order to establish whether these dimensions move together or are independent from each other. Results suggest that people perceive themselves as more similarto other members of society than what income-based aspects show. In particular, considering the whole sample, evidence of an increasing income distance between social groups is found, while no increase concerns inequality in perceptions. Consequently, the dynamics of perceptions can help explain, for example, the empirical evidence regarding the lack of reaction to the rise of economic disparities and the general emulative consumption behaviours associated with increasing inequality detected in some countries.
Keywords: D31; D63; I31; 330; inequality; perceived social position; social classes